2016
DOI: 10.1186/s12939-016-0315-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with violence and abuse of older adults in Mexico’s 2012 National Health and Nutrition Survey

Abstract: BackgroundFactors associated with violence and the abuse of older adults are understudied and its prevalence in Mexico has not been reported. The aim of this study was to identify the prevalence and factors associated with violence and abuse of older adults in Mexico.MethodsWe used Mexico’s 2012 National Health and Nutrition Survey, which included a sample of 8,894 individuals who are 60 years or older and who self-reported a negative health event related to robbery, aggression or violence in the previous 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
2
17
1
11
Order By: Relevance
“…Considerando os critérios de inclusão, foram analisados 13 artigos, verificando-se diferenças nas definições conceituais e na metodologia, descritas com maior detalhe adiante. [33][34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Métodosunclassified
See 2 more Smart Citations
“…Considerando os critérios de inclusão, foram analisados 13 artigos, verificando-se diferenças nas definições conceituais e na metodologia, descritas com maior detalhe adiante. [33][34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Métodosunclassified
“…Nos estudos analisados (Tabela 2), verificou-se que os anos com maior número de publicações sobre este fenômeno foram 2015 (n=3) e 2012 (n=3); e que foi nos EUA que houve maior número de contribuição para o conhecimento desta matéria. 28,30,35,37,39 Tabela 1. Escala de Newcastle-Ottawa adaptada para a avaliação da qualidade dos estudos, utilizando a definição de violência contra a pessoa idosa segundo a WHO 3…”
Section: Características Gerais Dos Estudosunclassified
See 1 more Smart Citation
“…In Mexico, a study with a sample of 8,894 older adults reported abuse in the twelve months prior to the study, highlighting verbal abuse (62.9%), followed by physical aggression (32.3%), especially against women (18.7%). Although research indicates a predominance of psychological and/or verbal abuse, the evaluation of the other types depends on more refined instruments (22) . In a systematic review of the literature, Dong (23) found a variety of studies on the subject and identified the prevalence of some forms of abuse against the older adult depending on the population, location, definition and method of research.…”
mentioning
confidence: 99%
“…Violence also has a social impact on the lives of the elderly, contributing to low self-esteem, social isolation and feelings of insecurity, reinforcing negative aspects of old age 14 . Studies [15][16][17] dealing with elder violence tend to analyze the elderly as victims of abuse in most cases by caregivers or relatives, and intimate partner violence is still a scarce approach in the literature. This fact may be embedded in the understanding that violence does not occur among elderly partners, masquerading as neglect or family violence, since the caregiver may be the intimate partner.…”
Section: Introductionmentioning
confidence: 99%